The Influence Of Mathematical Concept Understanding Ability, Mathematical Reasoning Ability And Problem Solving Ability On Students' Computational Thinking Ability - Simanjuntak, Ribka Kristina; Sinaga, Bornok; Ahyaningsih, Faiz (LPPM Universitas 17 Agustus 1945 Semarang, 2025)
This research examines how conceptual comprehension, mathematical reasoning, and problem solving affect computational thinking. 122 students from class XI SMA Negeri 1 Pematang Siantar were given essay assessments on conceptual comprehension, mathematical reasoning, problem solving, and computational thinking. AMOS version 21 was used to analyze the test using Structural Equation Modeling (SEM). This study found that conceptual understanding, mathematical reasoning, and problem solving have a positive and significant effect on computational thinking ability with a contribution of 0.528. This means that 52.8% and 47.2% of computational thinking abilities are built by these three abilities, depending on other variables.